Utilization of banana peel waste impregnated into PVA/Alginate polymeric beads for copper(ii) ion adsorption / Nov Irmawati Inda … [et al.] - Inda, Nov Irmawati; Satrimafitrah, Pasjan; Shiomori, Koichiro; Aprilia, Natasya (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Banana peel waste was impregnated into PVA/Alginate polymeric beads to increase the particle size. Thus, it can be easily separate from the aqueous solution after extraction. The morphology of PVA/Alginate polymeric beads impregnated with banana peel waste was observed using SEM. Mechanical strength, density, pH effect and effect of initial concentration of copper(II) ion also determined. Polymeric beads containing banana peel waste work-well at pH 4 and reached the equilibrium condition at higher initial concentration of copper(II) ion in the solution.